Performance Enhancement of Video Data Transmission in Vehicular Adhoc Networks - Vineeth, Nandhini; Guruprasad, H S (Journal of ICT Research and Applications, 2025)
The transmission of video frames among vehicles is a crucial global requirement in current road traffic conditions. Video data in vehicles may serve passengers with information as well as entertainment and, crucially, provide the drivers with dynamic information about the traffic conditions on the road ahead, assisting in reaching their destination safely at the earliest convenience using an optimal route. Intelligent Transportation System through its subsystem Vehicular Ad-hoc Networks (VANETs) make these necessities a reality. Inter-sessions carrying video data that exhibit multi-hop scenarios are encountered in the real world when people in a place of emergency communicate with the fire station/doctors/police. In such situations, the earlier the communication can occur, the smaller the damage. This work aimed to reduce the end-to-end delay (EED) experienced in VANETs when unicasting video streams among vehicles involved in inter-sessions by considering the packet delivery ratio (PDR) as a supporting parameter. The technique Network Coding was applied in VANETs and the possible recoder behaviors were simulated. An algorithm – Dynamic Recoder Recommender (DRR) – was designed and implemented to select an appropriate recoder on the fly in a path decided by the Adhoc On-Demand Vector routing protocol. This implementation outperformed the conventional network coding in terms of EED and PDR when applied with random recoders.